Discursive considerations of child care professional experience in early childhood teacher education: contingencies and tensions from teacher educators. Issue 4 (2nd October 2018) - Gibson, Megan; McFadden, Amanda; Zollo, Lynette
ABSTRACT: New education reforms in Australia, and elsewhere in the world, are calling for degree-qualified early childhood teachers to work in prior to school contexts, including child care. Yet, emerging research indicates that the majority of early childhood graduates are averse to work in child care, with a career desire to work in other contexts – primary, kindergarten, preschool. This paper reports on a pilot study that focused on early childhood teacher preparation, with attention to child care professional experience. Interviews with early childhood teacher educators, including program coordinators, focused on the decision making processes about the child care professional experience. Discourse analysis located some of the competing and complex discursive considerations, illuminating the contingencies and tensions that face early childhood teacher educators. The imperatives on reflective thinking and decision making in complex early childhood teacher education landscapes are illuminated. These contingencies and tensions have implications for the workforce they are charged to prepare, as policy imperatives call for teachers prepared and willing to work in child care.